Child and adolescent obesity: part of a bigger picture. Issue 9986 (20th June 2015) - Lobstein, Tim; Jackson-Leach, Rachel; Moodie, Marjory L; Hall, Kevin D; Gortmaker, Steven L; Swinburn, Boyd A; James, W Philip T; Wang, Youfa; McPherson, Klim
Summary: The prevalence of childhood overweight and obesity has risen substantially worldwide in less than one generation. In the USA, the average weight of a child has risen by more than 5 kg within three decades, to a point where a third of the country's children are overweight or obese. Some low-income and middle-income countries have reported similar or more rapid rises in child obesity, despite continuing high levels of undernutrition. Nutrition policies to tackle child obesity need to promote healthy growth and household nutrition security and protect children from inducements to be inactive or to overconsume foods of poor nutritional quality. The promotion of energy-rich and nutrient-poor products will encourage rapid weight gain in early childhood and exacerbate risk factors for chronic disease in all children, especially those showing poor linear growth. Whereas much public health effort has been expended to restrict the adverse marketing of breastmilk substitutes, similar effort now needs to be expanded and strengthened to protect older children from increasingly sophisticated marketing of sedentary activities and energy-dense, nutrient-poor foods and beverages. To meet this challenge, the governance of food supply and food markets should be improved and commercial activities subordinated to protect and promote children's health.